Assessing the Quality of Electronic Exams During the COVID-19 Pandemic - Zahra Zahedi; Hamid Salehiniya; Afagh Zarei; Hamid Abbaszadeh (Kerman University of Medical Sciences, 2022)
Background: Due to the widespread utilization of electronic exams, neglecting their quality is a major threat. Assessing the quality of electronic exams plays a decisive role in determining the efficacy of electronic learning.Objectives: This study aimed to assess the quality of electronic exams held at the beginning of the coronavirus disease 2019 outbreak.Methods: Following a cross-sectional design, this study included all electronic exams of the electronic test center of Birjand University of Medical Sciences during the academic year of 2020. Reliability, discrimination index (DI), and difficulty index (DIF) of exams were used to assess the quality.  Descriptive statistics and frequency distributions were used to describe the data.Results: Out of 101 E-exams, 59.4% had appropriate DIF, 61.4% had low DI, and 66.3% had unfavorable reliability. Also, 38.6% of exams had high DIF (easy questions). For all exams, the mean of DIF, DI, and reliability was 0.66±0.14, 0.28±0.08, and 0.56±0.31, respectively. The mean of DI (P= 0.30) and reliability (P= 0.09) was not significantly different based on faculty. The mean of DIF was significantly different according to the faculty (P=0.03).Conclusion: Concerning the quality of e-exams, most problems are related to the DI and reliability. It is recommended to hold empowerment workshops on how to design exam questions for faculty members to get them acquainted with strategies to increase the reliability and discrimination index of the exam.